Pengaruh Karakteristik Individu dan Karakteristik Pekerjaan terhadap Motivasi Kerja Perawat Rumah Sakit Umum Haji Medan - Siregar, Syukron Firdaus; Dewi , Mustika; Akbar, Aulia (Regress: Journal of Economics & Management, 2023)
The article aims to determine the influence of individual characteristics and work characteristics on the work motivation of nurses at Haji Medan General Hospital. Types of quantitative research with multiple linear regression data analysis techniques. The total population was 262 people with a total sample of 72 peoples. The results showed that individual characteristics have a positive and significant effect on the work motivation of nurses at Haji Medan General Hospital, job characteristics have a positive and significant effect on the work motivation of nurses at Haji Medan General Hospital, individual characteristics and work characteristics together have a positive and significant effect on the work motivation of nurses at Haji Medan General Hospital.